Inference of software agent a web-based fcm (fuzzy cognitive map) and dcn (dynamic cognitive network) software agent - Pua, Eng Heng. (2008)
The current techniques for constructing and analyzing FCMs are inadequate and infeasible in practice [l]. The web-based FCM/DCN software agent is designed to aid in the constructing and analyzing the inference result of a FCM/DCN. The construction of FCM is made easy to user by providing a web-based GUI for user to define the factors and impact functions between the factors. Through the process of editing and running the simulation, user can easily fine-tune the parameters of the FCM/DCN.